2019
DOI: 10.21273/hortsci14110-19
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Increasing Fines on Soil Physical Properties of U.S. Golf Association Sand

Abstract: Drainage is important to golf and athletic facilities trying to avoid lost play time. Native soil containing clay is sometimes incorporated into sand profiles with the intent to increase water and nutrient holding capacities. However, mixes high in silt and/or clay often have drainage problems. Research was conducted on soil physical properties from incremental 10% v/v additions of silt and clay (fines) to a U.S. Golf Association (USGA)-specification sand. Soils were evaluated based on volumetric water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…In past specifications, the textural class was not included, and it is unclear why it would be included now, especially in this ambiguous context. Reco mmendations that no more than Agricultural Research & Technology: Open Access Journal 10% of the rootzone is very fine sand, silt, or clay, agrees with Brown et al [5], who demonstrated the addition of more than 20% silt and clay retained excessive water in the rootzone making it unsuitable for play (Table 1); however, 20% and less should be acceptable. Erring on the side of caution in this instance may be preferable, thus, 10% is sufficient.…”
Section: Critique Of Usga Reco Mmendations For a Methods Of Putting G...supporting
confidence: 78%
See 3 more Smart Citations
“…In past specifications, the textural class was not included, and it is unclear why it would be included now, especially in this ambiguous context. Reco mmendations that no more than Agricultural Research & Technology: Open Access Journal 10% of the rootzone is very fine sand, silt, or clay, agrees with Brown et al [5], who demonstrated the addition of more than 20% silt and clay retained excessive water in the rootzone making it unsuitable for play (Table 1); however, 20% and less should be acceptable. Erring on the side of caution in this instance may be preferable, thus, 10% is sufficient.…”
Section: Critique Of Usga Reco Mmendations For a Methods Of Putting G...supporting
confidence: 78%
“…Porosity of the rootzone is reco mmended to fall between 35% and 55%, with air filled porosity at 40 cm tension of 15% to 30% and water filled porosity at 40 cm tension of 15% to 25%. Our research has shown all pure sands have water filled porosity below 15% at 40 cm tension, and most would fail to meet this requirement [5]. Addition of an organic amendment or native soil to the rootzone could increase the water content at this depth to acceptable levels; however, other properties could be adversely affected, resulting in the mix being unacceptable.…”
Section: Usga Reco Mmendations For Putting Green Construction 1993mentioning
confidence: 89%
See 2 more Smart Citations
“…The content of fines also affects the porosity of sand and its water holding capacity that is important for the growth of the grass and other plants on rootzones. The study by Brown et al (2019) showed that a considerable increase in fines in the rootzone mixtures; leads to increased water holding capacity of the material.…”
Section: Discussionmentioning
confidence: 99%